Efeitos do fogo sobre a estrutura de comunidades de abelhas e sobre redes de interações abelha-planta em áreas de canga no Parque Estadual da Serra do Rola Moça - Rosinalva da Cunha dos Santos (2013)
Natural and antropic fires are very common during the dry season in the Cerrado (Brazilian savanna) and are pointed as important transforming agents of the fauna and flora in this domain. For this reason, understanding how bees respond to these events is important for the conservation of their communities structure. Since the knowledge on the effects of fire on bees is meager and there are no studies on the effects of fires on the bee fauna of the Cerrado, this work was proposed to evaluate the influence of fire on the community structure of bees, comparing bee abundance and species richness and composition in burned and unburned areas of canga couraçada (shrubby vegetation on hardly sintered, iron-rich soil over 1000 m above sea level). We sampled six sites, three burned areas and paired with three adjacent unburned areas. Sampling started few weeks after a fire event and was repeated monthly for six months. Two sampling methods were employed: active sampling with hand net and pan-traps. Active sampling suggested greater average abundance and species richness in unburned areas, with significant interaction between treatment and month to the average richness and average abundance the interaction between these factors was marginally significant, it also revealed significant difference in species composition between burned and unburned areas in two of the three area-pairs; such results were associated with greater availability of floral resources in unburned areas. Samples obtained with pan-traps, revealed that there was not a pattern associated with the incidence of fire, with burned areas presenting larger average abundance and species richness, and the interaction treatments and month for average abundance and richness was not significantly different. With similarity of species between burned and unburned areas.